The answer is - 5.
That's because g(0) means "the value of the function g(x) for x = 0." Putting x = 0 in the expression (4 x - 5) simply gives 4*0 - 5 = - 5.
By the way, owing to a Yahoo! Answers quirk, your correctly written g(x) on the actual answer panel page appeared as G(x) in the main title for your question. This is no doubt due to some Yahoo! software error which renders the first letter of a question as a Capital Letter, whether it should or should not be so capitalised! I was glad to see that you at least had not intended to switch upper and lower cases on we responders, when seeking our answers.
Live long and prosper.
2007-01-02 15:08:31
·
answer #1
·
answered by Dr Spock 6
·
2⤊
0⤋
*The "x" variable represents a number/value. In this case, the problem gives us the number which, is "0" >
First: replace "0" with the "x" variable in the function >
g(0) = 4(0) - 5
g(0) = 0 - 5
g(0) = - 5
2007-01-02 15:13:39
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
1⤋
g(x) = 4x - 5
g(0) = 4(0) -5
g(0) = -5
It appear that you are having trouble with the substitution of the variable g(x) into an equasion. What you need to do is take the variable (x) and replace wherever it occurs in the equasion and then solve the equasion. The example I have shown above does this. I hope it helps.
2007-01-02 15:12:08
·
answer #3
·
answered by michael45672007 3
·
1⤊
1⤋
g(0) is equal to g(x) = 4x - 5 when x = 0, so plug in 0 for x and solve.
g(0) = 4(0) - 5
g(0) = -5
2007-01-02 15:10:03
·
answer #4
·
answered by drakeflare73 2
·
1⤊
0⤋
4(0)-5
0-5
-5
2007-01-02 15:12:20
·
answer #5
·
answered by 7
·
1⤊
0⤋
subsitute any 'x' with '0' to find g(0)
g(0) = 4(0) - 5
therefore g(0) = - 5
2007-01-02 15:12:55
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
g(0) = 4(0) - 5
g(0) = -5
2007-01-02 15:15:43
·
answer #7
·
answered by aeiou 7
·
0⤊
0⤋
g(x) = 4x - 5
g(0)=4*0-5
g(0)=-5
2007-01-02 15:10:00
·
answer #8
·
answered by yupchagee 7
·
1⤊
0⤋